TASAWUF IRFANI: SEBUAH UPAYA PENCAPAIAN ILMU PENGETAHUAN MELALUI PENCERAHAN KALBU - Riadil Jannah, Sitti (Universitas Islam Negeri Alauddin Makassar, 2021)
Irfani Sufism is an Islamic scientific paradigm with esoteric-gnostic dimensions. In acquiring knowledge, Irfani Sufism emphasizes the hudhuri dimension as a pillar in building an altar of knowledge within a person. The position of the heart in this context has a very strategic role so that enlightenment of the heart becomes a prerequisite in acquiring knowledge. Therefore, Irfani Sufism emphasizes the enlightenment of the heart from various shadows of heart disease that can hinder the acquisition of knowledge. Science is seen as something sacred so that one of the prerequisites for obtaining such knowledge is to purify the heart itself. The purer the human heart from various heart diseases that may manifest because of the love for various profane, pragmatic, and hedonic worldly mirages, the easier the knowledge can be obtained.